JUMLAH HEMOSIT TOTAL PADA UDANG VANAME (Litopenaeus vannamei) YANG DIBERIKAN TAMBAHAN TEPUNG BATANG PISANG PADA PAKAN - Adni Oktaviana; Dian Febriani (Jurnal Perikanan Unram, 2019)
This study aims to determine the total number of hemocytes and the survival of vaname shrimp (L. vannamei) which are fed with the addition of banana stem flour. This study consisted of three treatments with three replications. The experimental design used was a completely randomized design (CRD) at an error level of 5%. The treatments taken are the maintenance of vaname shrimp by feeding them with the addition of banana stem flour with a dose of 0 gr / kg of feed (A), maintenance of vaname shrimp by feeding them which is given the addition of banana stem flour with a dose of 4 gr / kg of feed (B) and maintenance of vaname shrimp by feeding them with the addition of banana stem flour at a dose of 6 gr / kg of feed (C). The parameters observed were survival rate (SR), total hemocyte count (THC) and water quality measurements. Water quality parameters measured consisted of temperature, dissolved oxygen (DO), pH value, and ammonia content. SR values ??obtained in this study were B (91.30%), C (88.40%) and A (81.15%), respectively.